On monitoring of mechanical characteristics of hot rolled S355J2 steel - D. Angelova; R. Yordanova; A. Georgiev; S. Yankova (Fracture and Structural Integrity)
Hot rolling normalization technology for producing sheets from a low-carbon steel, Steel S355J2, used in the Bulgarian Metallurgical Plant “STOMANA Industry SA” is under investigation. A newly introduced automatic application optimization procedure in this technology is an important step that leads to avoiding of traditional heat treatment, improving of steel mechanical characteristics, increasing of production efficiency, all resulting in high quality final products. On the basis of the final mechanical rolled-sheet characteristics - yield strengths, Re, ultimate tensile strengths, Rm, absorbed energies in impact tests, K, and elongations after fracture - some energy-stress and energy-stress-elongation constructions-spaces have been plotted. These spaces can be used for general evaluation of the applied rolling technology and for prediction of steel-sheet mechanical behaviour.